EKSISTENSI PENDIDIKAN PONDOK PESANTREN TERHADAP PERUBAHAN AKHLAK SANTRI - Nuryanto, Nuryanto (JURNAL TARBAWIYAH, 2014)
In the first time, the education of Boarding School is the institution that concern in attitude and religion in around of society. Every students in Boarding School have rule from their teacher, because of that every people belive that they can get good serve in that place. The rule in the Boarding School to make a control system in the attitude to every students, so the students that out of the rule can be controled by the teacher and get the treatment that make the students back to the rule and change the bad attitude to be a good attitude.Â Key Woed: the education of Boarding School